Functionalization of heterocyclic compounds using polyfunctional magnesium and zinc reagents - Knochel, Paul; Schade, Matthias A.; Bernhardt, Sebastian; Manolikakes, Georg; Metzger, Albrecht; Piller, Fabian M.; Rohbogner, Christoph J.; Mosrin, Marc (Beilstein Journal of Organic Chemistry, 2011)
In this review we summarize the most important procedures for the preparation of functionalized organzinc and organomagnesium reagents. In addition, new methods for the preparation of polyfunctional aryl- and heteroaryl zinc- and magnesium compounds, as well as new Pd-catalyzed cross-coupling reactions, are reported herein. Experimental details are given for the most important reactions in the of this article.
Keywords: cross-coupling; heterocycles; insertion; metalation; organomagnesium; organozinc